PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK GROUP INVESTIGATION DALAM PEMBELAJARAN IPS - ., Aisyah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This study aims to improve student learning outcomes through the application of the Cooperative Learning Technique Group Investigation Model IV-B students at SD Negeri 1 Kuta Binjei II semester 2017-2018 in Social Studies learning. This research is a classroom action research (CAR) conducted in two cycles, in each cycle, using several research procedures including, planning, implementation, observation and reflection. Data collection techniques used in research include, observation of teacher activities, student activities, and student learning outcomes tests, which are used to determine student learning outcomes after action. Student learning outcomes can be declared successful if the learning outcomes have reached KKM of 70. Classically a class has finished learning if classical completeness reaches 85% by applying the use of the Cooperative Learning Technique Group Investigation Model. Before learning by using the Group Investigation Technique Cooperative Learning Model the average score of students is 50.76. From the results of the analysis it was found that student learning outcomes experienced an increase from the first cycle of the formative test scores of students 67.50 to 78.50 in the second cycle and the level of students' mastery learning in the first cycle which was 46.67% to 93.33% on silkus II. The conclusion of this study is the use of Cooperative Learning Model Group Investigation techniques in social studies learning material impact of globalization can have a positive effect on improving learning outcomes of students of class IV-B SD Negeri 1 Kuta Binjei second semester of the school year 2017-2018.